Evaluation of ex vivo melanogenic response to UVB, UVA, and visible light in facial melasma and unaffected adjacent skin - Alcantara, Giovana Piteri [UNESP]; Cavalcante Esposito, Ana Claudia [UNESP]; Felicio Olivatti, Thaina Oliveira [UNESP]; Yoshida, Melissa Mari [UNESP]; Miot, Helio Amante [UNESP] (Elsevier B.V., 2020)
Background: The independent rote of solar radiation in the differential melanogenesis between melasma and adjacent skin is unknown. Objectives: To assess the melanogenic responses of skin with facial melasma and of the adjacent skin to UVB, UVA, and visible tight, in an ex vivo model. Methods: This was a quasi-experimental study involving 22 patients with melasma. Facial melasma and adjacent skin samples were collected and stored in DMEM medium, at room temperature. One fragment was placed under the protection from light, while another was exposed to UVB, UVA, and visible light (blue-violet component): 166 mJ/cm(2), 1.524 J/cm(2), and 40 J/cm(2), respectively. Subsequently, all samples were kept for 72 hours in a dark environment and stained by Fontana-Masson to assess basal layer pigmentation, dendrites, and melanin granulation. Results: Effective melanogenesis was observed in the basal layer in melasma and in the normal adjacent skin after all irradiations (p <0.01), with the following median increment: UVB (4.7% vs. 8.5%), UVA (9.5% vs. 9.9%), and visible light (6.8% vs. 11.7%), with no significant difference between anatomical sites. An increase in melanin granulation (coarser melanosomes) was observed only after irradiation with UVA and only in the skin with melasma (p= 0.05). An increase in the melanocyte dendrite count induced by UVB radiation was observed in both anatomical sites (p <= 0.05). Study limitations: Use of an ex vivo model, with independent irradiation regimes for UVB, UVA, and visible light. Conclusions: Melanogenesis induced by UVB, UVA, and visible tight was observed both in melasma and in the adjacent skin. The morphological patterns suggest that different irradiations promote individualized responses on the skin with melasma. (C) 2020 Sociedade Brasiteira de Dermatotogia.
Keywords: Melanosis; Photobiology; Ultraviolet rays